Pembuatan serbuk kering bermuatan jamur Phanerochaete chrysosporium - Dwina Moentamaria (Jurnal Teknik Kimia Indonesia, 2004)
Have been learned influence of ability of carrier media of white rot fungus of Phanerochaete chrysosporium (P.chrysosporium) for degradation of textile waste. The objective of this research to make dry powder P.chrysosporium with low water content mixedly is containing liquid media of inoculum and carrier media of flour dried  cassava and maizena . This drying powder prevent growing other contaminant and used by media of carrier in order to facilitate distribution to consumer go together ability of white rot fungus kept in the form of dry powder for a long time relative. P.chrysosporium grown at liquid media of Nitrogen Limited Media (NLM) during 4 days is so that obtained by extracelluler enzyme obstetrically is its highest Lignin Peroxide (Lip) which personating of degradation of an organic matter especially synthethic dyes. Variable used is ratio of liquid media which have been growed by P.chrysosporium to solid media that is 1:0,8; 1:1; 1:1,2; 1:1,4; drying times 2,3,4,5 hours by freeze dryer. Result of research obtained, carrier media of cassava flour by ratio 1:0,8, drying time 5 hours, a period of keeping 1 month moon able to degradation concentration of waste of textile as much 57,58 %. Carrier media of mixture of cassava and maizena flour by ratio 1:1,4, drying time of 5 hours, a period of keeping 1 month; moon able to degradation concentration of waste of textile as much 29,55 %.Key Words: Phanerochaete chrysosporium, Carrier Media, Dry PowderAbstrakDalam penelitian sebelumnya telah dipelajari pengaruh kemampuan media pembawa (carrier) yang bermuatan jamur pelapuk putih Phanerochaete chrysosporium (P.chrysosporium) untuk mendegradasi limbah tekstil. Penelitian ini bertujuan untuk membuat serbuk kering P.chrysosporium kadar air rendah dengan mencampurkan media cair yang berisi inokulum dan media pembawa tepung gaplek dan jagung. Serbuk kering dengan kadar air rendah dapat menghindari tumbuhnya kontaminan lain sehingga dapat digunakan setelah penyimpanan yang relatif lama. Produk serbuk kering lebih efisien digunakan karena memudahkan pendistribusian ke pengguna. Inokulum P.chrysosporium ditumbuhkan pada media cair Nitrogen Limited Media (NLM) selama 4 hari sehingga diperoleh enzim ekstraseluler dengan kandungan terbesarnya Lignin Peroksida (LiP) yang berperan sebagai pendegradasi zat organik terutama warna sintetis. Variabel yang digunakan adalah ratio media cair yang telah ditumbuhi P.chrysosporium terhadap media padat yaitu 1:0,8; 1:1; 1:1,2; 1:1,4; lama pengeringan 2,3,4,5 jam dengan freeze dryer. Hasil penelitian menunjukkan media pembawa tepung gaplek (ubi kayu) dengan ratio 1:0,8, waktu pengeringan 5 jam, masa simpan 1 bulan mampu menurunkan konsentrasi limbah tekstil sebanyak 57,58 %. Sedang media pembawa campuran tepung gaplek dan jagung  dengan ratio 1:1,4, waktu pengeringan  5 jam,  masa simpan 1 bulan mampu menurunkan konsentrasi limbah tekstil sebanyak 29,55 %.Kata Kunci : Phanerochaete chrysosporium, Media Pembawa, Serbuk Kering